Evaluating the effects of an algae-modified montmorillonite clay in diets contaminated With deoxynivalenol on nursery pig growth performance - Erceg, Jake A.; Frobose, Hyatt L.; Tokach, Michael D.; DeRouchey, Joel M.; Dritz, Steven S.; Goodband, Robert D.; Nelssen, Jim L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2014)
A total of 280 nursery pigs (PIC 327 × 1050, initially 21.9 lb and 35 d of age) were used in a 21-d growth trial to evaluate the effects of an algae-modified montmorillonite clay (MMi) on nursery pig performance when fed diets contaminated with deoxynivalenol (DON). Pigs were allotted to pens by weight, and pens were randomly assigned to 1 of 5 dietary treatments arranged in a 2 × 2 + 1 factorial with 7 pigs per pen and 8 pens per treatment. All experimental diets were pelleted. Mycotoxin analyses were conducted on the main ingredients at NDSU3 and LDA labs4, and these results were used in diet formulation. Naturally contaminated wheat (10.7 ppm DON) was used to produce diets with approximately 5 ppm DON. The 5 treatments consisted of 2 positive control diets that did not contain DON contamination with or without 0 or 0.50% MMi and 3 negative control diets that were contaminated with 5 ppm of DON and contained 0, 0.25%, or 0.50% MMi. No DON × MMi interactions were observed for the entire study. Overall (d 0 to 21), ADG, ADFI, and d 21 BW decreased (P < 0.001) in pigs fed DON-contaminated diets regardless of MMi addition. Feed efficiency was poorer (P < 0.001) for pigs fed diets with DON due, primarily to poor feed efficiency in the initial period (d 0 to 7). Pigs fed diets contaminated with DON had greater (P < 0.05) BW variation (CV) within pen on d 21. Although the addition of 0.5% MMi to diets restored (P < 0.02) ADFI from d 14 to 21, no other treatment differences were observed for MMi inclusion. In conclusion, this study suggests that including MMi will not offset reductions in nursery pig performance caused by high DON levels (> 5 ppm) when diets are fed in pellet form.
Keywords: Deoxynivalenol; Montmorillonite clay; Nursery pig; Vomitoxin